Different roles played by periostin splice variants in retinal neovascularization. (December 2016) - Nakama, Takahito; Yoshida, Shigeo; Ishikawa, Keijiro; Kobayashi, Yoshiyuki; Abe, Takaya; Kiyonari, Hiroshi; Shioi, Go; Katsuragi, Naruto; Ishibashi, Tatsuro; Morishita, Ryuichi; Taniyama, Yoshiaki
Abstract: Retinal neovascularization (NV) due to retinal ischemia is one of the major causes of vision reduction in patients with different types of retinal diseases although anti-vascular endothelial growth factor (anti-VEGF) therapy can partially reduce the size of the retinal NV. We recently reported that periostin plays an important role in the development of NV and the formation of preretinal fibrovascular membranes, but the role of the splice variants of periostin on retinal NV has not been determined. We examined the expressions of periostin splice variants in the ischemic retinas of a mouse model of oxygen-induced retinal NV. We also studied the function of periostin splice variants on retinal NV using periostin knock out mice, and the effects of anti-periostin antibodies on retinal NV. Our results showed that the expressions of the periostin splice variants were increased in ischemic retinas. The degree of increase of periostin lacking exon 17 was the highest among the periostin splice variants examined. Both genetic ablation of periostin exons 17 and 21 and antibodies for periostin exons 17 and 21 affected preretinal pathological NV. Inhibition of exon 17 of periostin had the greatest effect in reducing preretinal pathological NV. These findings suggest a causal link between periostin splice variants and retinal NV, and an intravitreal injection of antibody for exon 17 and exon 21 of periostin should be considered to inhibit preretinal pathological NV. Highlights: Expression patterns of periostin splice variants in ischemic retina were different. Exon 17 of periostin may promote both pathological and physiological angiogenesis. Exon 21 of periostin may promote only preretinal pathological neovascularization. Antibody for periostin splice variant can be a therapeutic agent for angiogenesis.